Digital Business Transformation in SMEs: A Case Study of Ash Scarf - Rita Anggraini Rahayu; Budi Eko Soetjipto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study meticulously analyzes the digital business transformation undertaken by Ash Scarf, a representative Small and Medium Enterprise (SME). The research meticulously highlights the strategic adoption and multifaceted utilization of digital marketing by Ash Scarf as a pivotal mechanism for business expansion, enhanced consumer outreach, and significant sales augmentation. To fortify these findings and contextualize them within broader academic discourse, a comprehensive bibliometric analysis of extant scholarly literature concerning digital marketing strategies pertinent to SMEs will be integrated, providing a robust understanding of prevailing trends and recognized best practices in this dynamic field.